Self-compassion : stop beating yourself up and leave insecurity behind - Neff, Kristin (New York : William Morrow, 2011)
'A book that teaches readers how to silence self-criticism and replace it with self-compassion in order to fulfill our highest potential and live happier, more fulfilled lives'--
Includes bibliographical references and index.
Keywords: Self-acceptance.; Compassion; Security (Psychology)